Time-dependent quantum mechanical treatment of He-CO inelastic scattering - Akpinar, S; Bulut, N; Gogtas, F (World Scientific Publ Co Pte Ltd, 2004)
The state-to-state and state-to-all reaction probabilities for He+CO(v,j) --> He+CO(v',j') reaction at zero total angular momentum have been calculated by using a time-dependent quantum wave packet method. The time-dependent method used is based on Fourier Grid and Discrete Variable Representation (DVR) techniques. The time-dependent propagation of the wave packet is accomplished by an expansion in terms of modified complex chebyshev polynomials. The results show that the He+CO reaction is not reactive in the studied energy range.
Keywords: inelastic scattering; quantum wavepacket; transition probabilities